Consumer Preferences of Tomato and Eggplant in Dili, East Timor - Sitorus, Lamdor Tiurmauli (2020)
Although vegetables are popularly consumed in East Timor, there are few studies on consumer behavior and their preferences, especially those focusing on the preferences of tomato and eggplant consumers in Dili, East Timor. This study aimed to identify consumer preferences in buying tomato and eggplant in Dili, Timor-Leste. The methodology used in this study to achieve the designated objectives included two stages of information gathering. The first one regarded the acquisition of secondary information through a wide literary revision. Such included both theoretical and empirical components, framing consumer behavior and their purchase preferences. During the second stage, a primary search was outlined through a questionnaire which was given to Dili based consumers, in local markets and supermarkets. The results allowed for relevant conclusions. Albeit difficulties and limitations in research, this study still permitted the development of suggestions and guidelines for future research.